The new Damascus document : the midrash on the eschatological Torah of the Dead Sea Scrolls : reconstruction, translation and commentary - Wacholder, Ben Zion. (Studies on the texts of the desert of Judah,, 2007)
This volume examines twelve ancient and medieval manuscripts, ten from the caves at Qumran and the two so called Damascus Documents from the Cairo Geniza, presenting a new organization and understanding of these texts. The twelve manuscripts are in a composite form under the title Midrash haTorah haAcharon (MTA), the Midrash of the Eschatological Torah, a title which opens a new window into the understanding of the Jewish literary tradition during the period of the Second Temple, prior to the development of the Talmud and Christianity. Following the composite Hebrew text are a full translation, notes and commentary elucidating the MTA in light of the new evidence provided by these texts and retranslation.